The use of XFEM to assess the influence of intra-cortical porosity on crack propagation. Issue 4 (12th March 2017) - Rodriguez-Florez, Naiara; Carriero, Alessandra; Shefelbine, Sandra J.
Abstract: This study aimed at using eXtended finite element method (XFEM) to characterize crack growth through bone's intra-cortical pores. Two techniques were compared using Abaqus: (1) void material properties were assigned to pores; (2) multiple enrichment regions with independent crack-growth possibilities were employed. Both were applied to 2D models of transverse images of mouse bone with differing porous structures. Results revealed that assigning multiple enrichment regions allows for multiple cracks to be initiated progressively, which cannot be captured when the voids are filled. Therefore, filling pores with one enrichment region in the model will not create realistic fracture patterns in Abaqus-XFEM.